Critical hospital social work practice - Burrows, Daniel (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Critical Hospital Social Work Practice sheds light on the fast-paced, high pressure role of the hospital social worker. At a time of public concern over the state of the NHS and the needs of a growing older population, the hospital social worker's job is more important than ever. Yet, it is poorly understood and often overlooked by policy makers, managers and other professionals"--
Part I. Key issues in hospital social work -- Hospital social work in context -- A brief history of hospital social work -- The current state of hospital social work -- Using research in social work -- Part II. An ethnographic account of hospital social work -- Social work in the 'iron cage' -- Is it still social work? -- The social work 'cuckoo' in the hospital 'nest' -- Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Medical social work -- England; SOCIAL SCIENCE / Social Work